(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, with the use of the moving boundary computational fluid dynamics method, we developed a new real-time optimal control method which can be used to find the optimal flapping mode of a fixed flapping plate. The results show that there is a 54.0% increase in the thrust obtained by the unsteady optimal flapping rule. In addition, to reduce the cost of computation and to have a better understanding of the flapping rule, the maximum velocity at the end tip of the flapping plate is taken as the objective functional, with which the thrust is increased by 22.9%.